PENGARUH PEMBERIAN Indigofera zollingeriana DALAM RANSUM TERHADAP PERFORMA ITIK PEKING - Muhammad Tholib Zaqi, Riyanti, Rudy Sutrisna, dan Dian Septinova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This study aimed to determine the effect of Indigofera zollingeriana in the ration on performance of Peking ducks. This study used Completely Randomized Design (CRD) with five treatments and four replications, each replication consisted of one duck with a number of ducks of 20 (unsex) with a diversity coefficient of 8.6%. The treatment given in this study was the diference of the level of Indigofera zollingeriana in the ration, those were R0: 0%, R1: 4%, R2: 8%, R3: 12% and R4: 16%. The study was conducted for seven weeks in February - April 2018 in the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The variables observed were feed consumption, body weight gain, and feed conversion. The results showed that Indigofera zollingeriana in the ration given to Peking ducks from 2--7 weeks with R0 0%, R1 4%, R2 8%, R3 12%, and R4 16% did not significantly affected (P> 0 05) on feed consumption, body weight gain, and feed conversion. The effect of Indigofera zollingeriana up to 16% in Peking duck rations had good protein quality and could be used as a feed ingredient for protein sources to increase body weight gain with the same protein content of rations of 18%. Keywords: Indigofera zollingeriana, Performance, Peking duck